2014
DOI: 10.5937/industrija42-5263
|View full text |Cite
|
Sign up to set email alerts
|

10.5937/industrija42-5263 = The quality of business communications depending on attachment style, social emotional competences and personality traits

Abstract: The main goal of this paper is to examine connection between (Takšić, Moharić & Munjas, 2006), Experiences in Close Relations (Kamenov & Jelić, 2003), Personality Questionnaire (Zuckerman, 2002), Humor styles Questionnaire (Martin, Puhlik-Doris, Larsen, Gray & Weir, 2003) and Satisfaction With Life Scale (Diener, Emmons, Larsen & Griffin, 1985

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the research from 2014 and 2015 (Nikić et al, 2014a(Nikić et al, , 2015, it was obtained that managers as well as management students have higher scores on all three scales of emotional intelligence. It was shown that respondents with higher scores on emotional intelligence, show greater activity and sociability and lover levels of neuroticism and aggression, which is important for teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…In the research from 2014 and 2015 (Nikić et al, 2014a(Nikić et al, , 2015, it was obtained that managers as well as management students have higher scores on all three scales of emotional intelligence. It was shown that respondents with higher scores on emotional intelligence, show greater activity and sociability and lover levels of neuroticism and aggression, which is important for teamwork.…”
Section: Discussionmentioning
confidence: 99%